The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1038/bjc.1990.184
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical assessment of cellular proliferation markers in head and neck squamous cell cancers

Abstract: Summary Prognostic information is essential for the evaluation, judgement and optimal treatment of patients with squamous cell cancers (SCCs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 40 publications
5
49
0
3
Order By: Relevance
“…The immunocytochemical pattern of EGF receptor expression in the tissues from which the cell lines were derived in the present study was differentiation related in that there was marked staining in basal epithelial cells and diminished reactivity in areas of squamous differentiation; this confirms previous observations (Partridge et al, 1988;Sakai et al, 1990;Kearsley et al, 1990;Shirasuna et al, 1991 were evident in the present study, and it may be that radioimmunoassays would clarify this situation.…”
Section: Discussionsupporting
confidence: 81%
“…The immunocytochemical pattern of EGF receptor expression in the tissues from which the cell lines were derived in the present study was differentiation related in that there was marked staining in basal epithelial cells and diminished reactivity in areas of squamous differentiation; this confirms previous observations (Partridge et al, 1988;Sakai et al, 1990;Kearsley et al, 1990;Shirasuna et al, 1991 were evident in the present study, and it may be that radioimmunoassays would clarify this situation.…”
Section: Discussionsupporting
confidence: 81%
“…Extensive scoring methods have been designed in an attempt to increase the objectivity of these parameters [34][35][36][37]. Other ancillary parameters, such as mitotic index, DNA content, Ki-67, proliferation cell nuclear antigen, and bromodeoxyuridine labelling index, may be used in an attempt to identify new prognostic indicators [38,39]. But, due to financial constraints, availability of advanced parameters along with advanced technology for carrying out research in the developing countries, like us, are the real limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A severe overexpression of EGFR may correspond with a wide expression of receptors on the cell surface, leading to a constitutive activation of the downstream effectors, with generation of a marked, proliferative ligand-mediated signal. In fact, a specific clinical study has demonstrated a positive correlation between the intensity of EGFR expression and the nuclear proliferative index, Ki-67, in head-and-neck SCC (21). Tumour cells increase their proliferative activity, and the repopulation effect derived from this mechanism may counteract the effects of radiotherapy (22,23).…”
Section: Biology Of Nmsc and The Rationale For Using Targeted Therapymentioning
confidence: 99%